2006
DOI: 10.1111/j.1439-037x.2006.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Placement of Slow‐release Fertilizer (Lime Nitrogen) Applied at Different Rates on Growth, N2 Fixation and Yield of Soya Bean (Glycine max [L.] Merr.)

Abstract: A new fertilization method with deep placement of slowrelease N fertilizers, such as coated urea and lime nitrogen (LN) (calcium cyanamide) at 20 cm depth was found to promote soy bean seed yield. In the present study, the effect of deep placement of LN was investigated on different parameters such as growth, N accumulation, N 2 fixation activity and yield of soy bean by applying LN at different rates in the rotated paddy field of Niigata, Japan. In addition to the basal fertilizer, ammonium sulphate (16 kg N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Nitrogen is a basic component of amino acids, proteins, nucleic acids, and quite a lot of other metabolites, which are all essential for the growth and development of plants. It is also documented that CaCN 2 application affects nitrogen plant availability and accumulation [29]. Our results on N fruit concentration revealed that a decrease in N fruit content can be achieved using the highest CaCN 2 dosage.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nitrogen is a basic component of amino acids, proteins, nucleic acids, and quite a lot of other metabolites, which are all essential for the growth and development of plants. It is also documented that CaCN 2 application affects nitrogen plant availability and accumulation [29]. Our results on N fruit concentration revealed that a decrease in N fruit content can be achieved using the highest CaCN 2 dosage.…”
Section: Discussionsupporting
confidence: 61%
“…Although there are findings that the application of CaCN 2 or other stabilized fertilizers containing nitrification inhibitors (NIs) can increase yield in potato (Solanum tuberosum L.) [28], soybean [Glycine max (L.) Merr.] [29], maize (Zea mays L.] [30], and wheat (Triticum aestivum L.) [31]. Hu et al [32] report that the use of NIs does not significantly influence the yields of several arable crops.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in the introduction section, crack fertilization is an application of the traditional concept of deep layer fertilization (Takagi et al, 1963). Takahashi and his coworkers (eg., Takahashi et al, 1991;Kaushal et al 2004Kaushal et al , 2006Kaushal et al , 2007 reported a series of experiments on deep layer fertilization. The major difference between the current deep layer fertilization (although not really adapted in the present soybean cultivation) and crack fertilization is whether the roots are cut during plant growth or not.…”
Section: Signifi Cance Of the Crack Fertilization Techniquementioning
confidence: 99%
“…For example, enhancement of nitrogen fi xation by a cultivation technique, not by the genetic improvement such as the use of supernodulating soybean cultivars (Takahashi et al, , 2005Nakamura et al, 2010), is one of the potential targets to improve soybean yield in Japan. In this paper, we report a new method of enhancing soybean nodulation by a cultivation technique called "crack fertilization" which is a combination of two existing concepts; deep layer fertilization (Takagi et al, 1963;Takahashi et al, 1991;Kaushal et al, 2004Kaushal et al, , 2006Kaushal et al, , 2007Watanabe et al, 2007) and subsoiling during soybean growth (Hamada et al, 2003;Ochiai et al, 2004;Iijima et al, 2005;Honjo et al, 2007). Deep layer fertilization is an old concept (eg; Takagi et al, 1963) that has been well tested, and subsoiling during soybean growth is a technique that was first tested at the Aichi Agricultural Research Center in 2001 (Hamada et al, 2003).…”
mentioning
confidence: 99%
“…Tewari et al (2004) and Kaushal et al (2005) reported that the deep placement of slow-release nitrogen fertilizers allowed plants to maintain a higher nitrogen concentration in the shoot organs and roots (Tewari et al 2004;Kaushal et al 2005). Kaushal et al (2006) indicated that the application of slow-release fertilizer at a depth of 20 cm could improve soybean yield (Kaushal et al 2006). These researches showed that nitrogen had a certain role in promoting soybean growth.…”
Section: Relationship Between Soil Porosity and Root Weight And Lengthmentioning
confidence: 99%